2019
DOI: 10.1155/2019/8315845
|View full text |Cite
|
Sign up to set email alerts
|

TF-343 Alleviates Diesel Exhaust Particulate-Induced Lung Inflammation via Modulation of Nuclear Factor-κB Signaling

Abstract: Inhalation of diesel exhaust particulate (DEP) causes oxidative stress-induced lung inflammation. This study investigated the protective effects of TF-343, an antioxidant and anti-inflammatory agent, in mouse and cellular models of DEP-induced lung inflammation as well as the underlying molecular mechanisms. Mice were intratracheally instilled with DEP or vehicle (0.05% Tween 80 in saline). TF-343 was orally administered for 3 weeks. Cell counts and histological analysis of lung tissue showed that DEP exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 56 publications
3
22
0
Order By: Relevance
“…It is also important to note that many urban regions worldwide exceed 100 μg/m 3 daily PM 2.5 levels [ 80 ]. While the dose chosen for the current study may be higher than that experienced by typical human environmental exposures, the (inflammatory) findings in the lung are in agreement with previous DEP-exposure studies [ 79 , 81 , 82 ]. Furthermore, the use of this DEP material is not necessarily representative of all traffic- or industry-generated PM, by current engine standards.…”
Section: Discussionsupporting
confidence: 87%
“…It is also important to note that many urban regions worldwide exceed 100 μg/m 3 daily PM 2.5 levels [ 80 ]. While the dose chosen for the current study may be higher than that experienced by typical human environmental exposures, the (inflammatory) findings in the lung are in agreement with previous DEP-exposure studies [ 79 , 81 , 82 ]. Furthermore, the use of this DEP material is not necessarily representative of all traffic- or industry-generated PM, by current engine standards.…”
Section: Discussionsupporting
confidence: 87%
“…Numerous researchers have investigated the associations between air pollution and health risk. In our previous study, a DEP-treated murine model and DEP-stimulated AM demonstrated that DEP induce lung in ammation by modulating the NF-kB signaling pathway [21]. However, the molecular mechanisms involved are still not completely understood.…”
Section: Discussionmentioning
confidence: 98%
“…DEP or PM exposure induces cell damage via ROS-mediated oxidative stress [5,21,24]. To determine whether oxidative stress mediates DEP-induced ER stress and in ammatory responses, we evaluated cytotoxicity and reactive oxygen species (ROS) production via MTT assay and DCF-DA uorescence intensity measurement, respectively.…”
Section: Effects Of Cell Viability and Oxidative Stress On Dep Stimulmentioning
confidence: 99%
“…Female Balb/c mice (Orient Bio, Seongnam, Korea) weighing 16.10 ± 0.52 g were housed in a temperature-controlled room ( [22]. During the in vivo experiment, the total amount of exposure is 75, 150, and 300 µg per mouse.…”
Section: Animalsmentioning
confidence: 99%
“…# p < 0.05 or ### p < 0.001 vs. control.2.6. Effects of Cell Cytotoxicity and Oxidative Stress on DEP Stimulation in AMDEP or PM exposure induces cell damage via reactive oxygen species (ROS)-mediated oxidative stress[5,22,23]. To determine whether oxidative stress mediates DEP-induced ER stress and inflammatory responses, we evaluated cytotoxicity and ROS production via 3-(4,5 dimethylthiazol-…”
mentioning
confidence: 99%